Studies of some short conjugation length polymeric light-emitting diode materials and their blends - Liau, Chu Yaw. (2008)
This thesis is mainly divided into five chapters. Chapter 1 gives an overview of light-emitting materials which in particular focuses on the PPV derivatives and their electrical-optical properties. Chapter 2 describes the synthesis of an intrinsically soluble copolymer, which has well defined substituted 2 Vi p-phenylenevinylene units alternating hexanedioxy blocks. The polymer is characterized by *H NMR, FTIR, UV-vis and fluorescence technique. Thermal properties are investigated with DSC and TGA under nitrogen atmosphere. The single-layer light-emitting diode device fabricated that has a simple ITO/polymer/Al configuration shows typical diode behaviour. Photodegradation of the copolymer is also studied by applying high-intensity UV irradiation as well as low-intensity irradiation at a fixed wavelength to the polymer film.